(untitled) (Journal of Pharmaceutical Negative Results, 2011)
England's public health system is undergoing significant change at the moment. The best strategies for addressing the persistent health disparities in British society and around the world have recently received renewed attention. Using cardiovascular disease (CVD) as a case study, we investigated the present experiences of those involved in decision-making to reduce health inequalities in order to examine the opportunities and difficulties facing England's new public health system. Techniques:Three focus groups and forty semi-structured interviews were used in our extensive qualitative study. Participants included public health academics, consultant cardiologists, national guideline managers, members of guideline development groups, civil servants, CVD third sector staff, Primary Care Trust and Local Authority employees (in a variety of roles), and general practice commissioners.Conclusions: It is imperative that the impact on the social determinants of health and health inequalities be used to gauge the cost- effectiveness and efficacy of all new and current public health policies and services. The complex evidence needed to compare various prevention and service delivery models is largely provided by researchers. Public health professionals must become leaders in order to advocate for central government to play a significant role in changing social norms and to draw attention to health disparities as a problem that requires resources, workforce capacity, and attention.